Chinese MSMEs internationalization in Latin American markets under the Belt and Road Initiative - Estrader, Joaquín; Zottele, Esteban (Latin American Journal of Trade Policy, 2023)
Micro, small, and medium enterprises (MSMEs) is an essential topic for business research and development policies. By reviewing previous literature and macroeconomic data, and following a deductive method, this study explains MSMEs’ contribution to national development, that is, a positive effect in terms of employment, regional economies, technological innovation, andincome distribution. In addition, we focus on Chinese MSMEs’ internationalization and competitive advantages in Latin American markets as a natural extension of the 21st Century Maritime Silk Road. Additionally, we explain the essential role of the Belt and Road Initiative in Chinese companies’ internationalization, particularly in building a platform for MSMEs operations in Latin America and the Caribbean. After conclusions we suggest further research directions.